ZAKAT SAHAM MNC SEKURITAS CABANG BANDUNG DALAM PERSPEKTIF FIQH TABARRU': ZAKAT ON SHARES OF MNC SECURITIES BRANCH BANDUNG IN THE PERSPECTIVE OF FIQH TABARRU' - Muzaki, Amar; Arifin, Tajul; Yuniarti, Vinna Sri (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2021)
Share zakat is a development object of zakat mal. With the increase in stock investors, zakat shares have high potential. MNC Sekuritas has a stock zakat feature as a zakat service with a stock object in collaboration with Rumah Zakat as amil zakat fund manager. However, zakat on shares is not for all shares listed on the IDX. This study aims to determine, describe, and analyze the criteria for shares that can be zakat and how the practice of implementing zakat shares at MNC Sekuritas Bandung is based on a review of sharia economic law. This research was conducted with a descriptive method, namely describing and reviewing the implementation of stock zakat at MNC Sekuritas Bandung. Sources obtained from the provisions relating to zakat shares from the MNC Sekuritas Bandung. This study concludes, shares that can be used as objects of zakat must be included in the Sharia Securities List (DES) and obtained lawfully so that not all shares can be zakated as not all assets can be zakat, the implementation of zakat shares at MNC Sekuritas Bandung is the same as the implementation of zakat in general and its implementation also easy and efficient. According to a review of sharia economic law, the implementation of zakat shares at MNC Sekuritas Bandung is based on sharia provisions and principles terms, and pillars. Zakat saham merupakan pengembangan objek zakat mal. Bertambahnya investor saham, zakat saham memiliki potensi tinggi. MNC Sekuritas memiliki fitur zakat saham sebagai layanan zakat dengan objek saham bekerja sama dengan Rumah Zakat sebagai amil pengelola dana zakat. Namun zakat saham tidak untuk semua saham yang terdaftar di BEI. Penelitian ini bertujuan untuk mengetahui, mendeskripsikan, serta menganalisis kriteria saham yang dapat dizakatkan serta bagaimana praktik pelaksanaan zakat saham di MNC Seuritas Bandung berdasarkan tinjauan fiqh tabarru. Penelitian ini dilakukan dengan metode deskriptif, yaitu memaparkan dan meninjau pelaksanaan zakat saham di MNC Sekuritas Bandung. Sumber diperoleh dari ketentuan yang berkaitan dengan zakat saham dari pihak MNC Sekuritas Bandung. Hasil penelitian ini ditemukan bahwa saham yang dapat dijadikan objek zakat haruslah masuk Daftar Efek Syariah (DES) dan diperoleh dengan halal sehingga tidak semua saham dapat dizakatkan sebagaimana tidak semua harta dapat dizakati. Selain itu, pelaksanaan zakat saham di MNC Sekuritas Bandung sama dengan pelaksanaan zakat pada umumnya serta pelaksanaanya pun mudah dan efisien. Kesimpulannya, pelaksanaan zakat saham di MNC Sekuritas Bandung telah sesuai dengan ketentuan serta prinsip syariah baik dari segi syarat maupun rukun.